The church faces death : ecclesiology in a post-modern context - Jinkins, Michael, 1953- (Oxford University Press, 1999)
Ecclesiology (the theology of the church) is a neglected topic in contemporary theology. At a time when the institutional churches are experiencing dramatic decline, says Michael Jinkins, we need a new understanding of what the church is. In this work, Jinkins challenges the church to rediscover its vocation, to follow Jesus Christ even at the risk of its institutional survival. In the face of a variety of perceived threats to its future, he reminds us that the church is most alive and attractive when it forgets about itself and its safety. The ecclesiology Jinkins puts forward is born from a.